Atkins: eat right, not less : your guidebook for living a low-carb and low-sugar lifestyle - Heimowitz, Colette (Atkins, 2017)
"Beautifully illustrated and filled with 100 whole food recipes and simple solutions for eating the foods we love in a healthier way, this brand-new Atkins guide focuses on eating right--not less--to achieve weight management goals and improve your overall health. For more than forty years, Atkins has been a leading brand, using proven scientific research to help hundreds of thousands of people achieve weight loss and weight management goals on a lower-carb diet. But while many Americans would like to lose weight, most don't want to adhere to a strict program. Discovering a healthy, sustainable way of eating that you can live with beats yo-yo dieting that only leaves you frustrated and discouraged. Atkins: Eat Right, Not Less offers choices and helps you find the level of carbohydrate consumption that you will be able to sustain in Atkins's first four-color hardcover guidebook. By making small adjustments to the foods you already eat, you can ease into a healthier lifestyle while still making a huge impact on your health and weight. Detailed information about the popular Atkins 40 approach (a favorite of Alyssa Milano and Kim Kardashian, and one of the Most Googled Diets of 2016), and the new flexible, personalized Atkins 100, Atkins: Eat Right, Not Less also provides step-by-step directions for those of us who need a more structured program with the original Atkins 20 approach, as well as meal plans for all three levels, grocery lists, and 100 simple and delicious recipes to kick-start your new lifestyle"--